PABLO BOCZKOWSKI: FOR THE REVISION OF THEORIES AND A NEW FOCUS ON AUDIENCES - Crispim da Fontoura, Marcelo (Brazilian Creative Industries Journal, 2022)
Pablo Boczkowski, professor at Northwestern University, has an influential career in Journalism Studies. In his first book, Digitizing the News, Boczkowski has described the early efforts of newsrooms to deal with digital media. His latest book, Abundance, is based on 158 interviews with media consumers in Argentina and analyzes how they establish routines and strategies over media. In this interview, Boczkowski discusses his legacy, the challenges that a new information environment poses to classic theories, and his focus on the research of audiences.